Cardiac magnetic resonance left atrioventricular coupling index as a prognostic tool in hypertrophic cardiomyopathy - Jinyang Wen; Junhao Tu; Xinwei Tao; Yuanyuan Tang; Zhaoxia Yang; Ziyi Pan; Yi Luo; Chunlin Xiang; Dazhong Tang; Lu Huang; Liming Xia (ESC Heart Failure)
Abstract Aims A novel marker left atrioventricular coupling index (LACI) has been proved to be associated with cardiovascular events in patients without history of cardiovascular disease. However, the studies on cardiac magnetic resonance‐derived LACI in hypertrophic cardiomyopathy (HCM) patients are limited, and the prognostic value of LACI has still not been studied thoroughly, so we aimed to explore the association between LACI and adverse clinical outcomes in HCM patients. Methods A total of 206 HCM patients underwent cardiac magnetic resonance examination were retrospectively enrolled. LACI is defined by the ratio between the left atrial (LA) volume and the left ventricular (LV) volume in LV end‐diastolic phase. The composite endpoint was categorized into death‐related, heart failure‐related, and arrhythmia‐related events, reflecting mortality risk, heart failure progression, and arrhythmia burden, respectively. Receiver operating characteristics curve analysis was used to determine the optimal cut‐off value for LACI to distinguish HCM patients at high risk of adverse clinical outcome. Multivariable Cox regression models were built including significant clinical variables, LA ejection fraction (LAEF), LA volume index (LAVI), late gadolinium enhancement (LGE) extent and LACI. The improvement of discrimination by adding LACI to a clinical model was assessed using C‐statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). Results Thirty‐four HCM patients reached the endpoint during a median follow‐up time of 60 [interquartile range (50–68)] months. In the multivariate Cox regression analysis, LACI [hazard ratio 1.054, 95% confidence interval (CI): 1.037, 1.071; P < 0.001] was an independent predictor of the composite events after adjustment for age and atrial fibrillation. Then 40.09% was identified as an optimal cut‐off for LACI in the risk stratification. Integrating LACI to the clinical model yielded higher C‐statistic 0.892 with 95% CI (0.861, 0.922) compared with LA diameter, LAEF, LAVI and LGE extent, providing an improvement in prediction of high‐risk patients (NRI = 0.627, 95% CI: 0.112–0.934; IDI = 0.295, 95% CI: 0.016–0.709). Conclusions LACI is an independent risk factor for clinical adverse outcome and is superior to conventional LA parameters and LGE extent for the identification of high‐risk HCM patients.